1972
DOI: 10.1002/anie.197202901
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the Cycloaddition of 1,3‐Diphenyl‐2‐azaallyllithium to Alkenes at 0 °C

Abstract: munication on a total synthesis16] we now publish our results on a biogenetically oriented indole-camptothecin rearrangement.Using the easily accessible indolic compound (3)"l as starting material, the indole-quinoline conversion could be carried out in two simple steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Reaction of phenanthrene with 1 HMPA gave the 9,10dehydro 1:1 adduct 10. Since 10 must be formed by dehydrogenation of the corresponding 9,10-dihydrophenanthrene (11), and atmospheric oxygen is known to convert dihydrophenanthrenes to phenanthrenes,11 we attempted but failed to isolate the initial adduct 11 by carrying out all experimental operations under nitrogen. Since unsubstituted 9,10-dihydrophenanthrene also was detected in the reaction mixture, 11 may have produced 10 by hydrogen transfer to phenanthrene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction of phenanthrene with 1 HMPA gave the 9,10dehydro 1:1 adduct 10. Since 10 must be formed by dehydrogenation of the corresponding 9,10-dihydrophenanthrene (11), and atmospheric oxygen is known to convert dihydrophenanthrenes to phenanthrenes,11 we attempted but failed to isolate the initial adduct 11 by carrying out all experimental operations under nitrogen. Since unsubstituted 9,10-dihydrophenanthrene also was detected in the reaction mixture, 11 may have produced 10 by hydrogen transfer to phenanthrene.…”
Section: Resultsmentioning
confidence: 99%
“…The former was isolated by GLC on column A at 290 °C, but the latter decomposed during attempted isolation. The compound with m/e 298 was identified as r-l,i-2,e-4-triphenylcyclopentane (2) by its 220-MHz NMR spectrum:8 IR (C2C14) 3100 (m), 3080 (m), 3040 (s), 2950 (m), 1600 (s), 1500 (s), 1450 (s), 1060 (m); mass spectrum m/e (rel intensity) 298 (55), 207 (11), 194 (54), 193 (100), 180 (11), 179 (27), 178 (23), 168 (20) , 165 (43).…”
Section: -Phenylallyltriphenyltin (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…45, 46 Tsuge, Kanemasa, and co-workers reported the first example of a nonstereospecific cycloaddition of a semistabilized 2-azaallyl anion with Z-stilbene, clearly indicative of a stepwise pathway (see 9 → 11 in Scheme 3 above). 45, 46 Tsuge, Kanemasa, and co-workers reported the first example of a nonstereospecific cycloaddition of a semistabilized 2-azaallyl anion with Z-stilbene, clearly indicative of a stepwise pathway (see 9 → 11 in Scheme 3 above).…”
Section: Mechanism and Stereoselectivitymentioning
confidence: 99%
“…Kauffmann proposed in 1972 that the cycloadditions of 1,3-diphenyl-2-azaallyllithium with E-and Z-stilbene were concerted processes based on their stereospecificity (Scheme 19), but recognized that a stepwise intermediate analogous to 78 might be involved as long as bond rotations were slow relative to ring closure. 45,46 Tsuge, Kanemasa, and co-workers reported the first example of a nonstereospecific cycloaddition of a semistabilized 2-azaallyl anion with Z-stilbene, clearly indicative of a stepwise pathway (see 9 → 11 in Scheme 3 above). 5 We have found that most of the cycloadditions of nonstabilized 2azaallyllithiums proceed with retention of the anionophile geometry, but we have found a few examples of non-stereospecific additions, again involving Z-stilbene (e.g.…”
Section: Mechanism and Stereoselectivitymentioning
confidence: 99%